ESTETIKA PADA FASAD BANGUNAN BENTENG VAN DER WIJCK DI KEBUMEN - Triono, Ade; Rahayu, Tuntun (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
This research is entitled Aesthetics of the Van Der Wijck Fortress building in Kebumen. Van der Wijck Fort isa Dutch colonial heritage building located in the Gombong SECATA (Tamtama Candidate School) complex whichis located at Jalan Sapta Marga Gombong. Aesthetics in architecture is a visual art that is a value that pleases theeye and the mind, namely the value of pleasant forms and expressions. The purpose of this paper is for the publicto know the value of architectural art contained in the Van der Wijck Fort, both in the arrangement of the roomsand the materials for the building of the fort. The data analysis technique uses qualitative data analysis whichconsists of data reduction, data presentation, and conclusion drawing. The result of this research is that thearchitectural art value of Van Der Wijck Fortress is very unique, in terms of the shape of this fort is in the form ofan octagonal or an octagonal, from the facade of the building it is also unique in the window and door openings,namely a semicircle, the wall thickness is 1.4 meters so that the fort building is very sturdy, flat material usingbricks, including the roof on the fort also uses brick materia